Conflict Mapping Analysis and Description of Conflict over Oil Palm Plantation Land between the Community of Senama Nenek Village and PTPN V Sei Kencana in Kampar Regency - Kausar, Kausar; Zaleha, Zaleha; Andriani, Yulia (Politeknik Pertanian Negeri Payakumbuh, 2022)
The conflict in the plantation sector involving the community and the company in the Senama Nenek Village occurred because of a dispute of an area of 2,800 hectares which had been acknowledged by both parties, the people of Grandma Senama Village and PTPN V Sei Kencana. This difference in opinion caused the public to make complaints to local governments. This study aims to overcome plantation conflicts and describe plantation conflicts that occur between the people of Senama Nenek Village and PTPN V Sei Kencana. The key informants of this study found 16 people consisting of 12 key informants from the community and 4 key informants from stakeholders. This study uses a qualitative descriptive analysis with triangulation. Based on the results of the study, it was found that the parties involved in mapping the plantation conflict consisted of the Senama Nenek Village government, the Tapung Hulu District Government, the Kampar Regency and Riau Province Plantation Service, the Kampar Regency, and Riau Province Land Agency, the Kampar Regency Government, the Kampar Regency DPRD. , the Regent of Kampar, the Regional Government of Riau Province, the Governor of Riau, the Ministry of SOEs, and the President of the Republic of Indonesia. The plantation conflict that occurred among the community, company, and local government is related to the use of custom land covering an area of 2,800 ha. Both parties continue to carry out activities even though they recognize each other's land ownership. Lately, the warring parties have returned to normal because the disputes between the parties can be resolved thanks to the leadership of the Ninik Mamak figures and the group board from the company.